PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI BERBANTUAN ARTIFICIAL INTELLIGENCE (AI) UNTUK MAHASISWA PIAUD IAIN CURUP - Meri Hartati; Aulia Rahmasari (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2025)
The purpose of this study is to produce prospective Early Childhood Education teachers, PIAUD Study Program IAIN Curup in providing various courses have good educational science insights and are creative in making learning media for early childhood. This study uses Development (R&D) with the ADDIE approach, which includes 5 stages: (1) Analysis stage, (2) Product design stage, (3) Product development, (4) Feasibility test stage, and (5) Evaluation stage. The results of this study are animated videos of early childhood social and emotional development teaching materials integrated with Islamic values. This teaching material received a very positive response and was considered very suitable for use. This is evidenced by the results of validation by experts (material experts, language experts, and media experts) who obtained an average score of 89% with the category "very suitable". Furthermore, early childhood sports and gymnastics teaching materials were tested on a small scale with a percentage of 85%, and on a large scale with a percentage of 87%, both of which were categorized as very suitable. This shows that early childhood sports and gymnastics teaching materials based on Islamic values are very suitable for use.